STRATEGI GURU DALAM MENGATASI HAMBATAN KOMUNIKASI SOSIAL : STUDI KASUS DI PAUD PERMATA BUNDA - Yayuk Listiyani; Indah Lestari; Mochamad Widjanarko (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Social communication skills play a crucial role in early childhood development. However, in early childhood education (PAUD) learning practices, children still experience difficulties interacting socially, expressing opinions, and participating in group activities. This study aims to identify barriers to social communication in early childhood, examine the strategies teachers employ to address these barriers, and analyze the impact of these strategies on children's social communication development at Permata Bunda PAUD. The study employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation with teachers and children experiencing barriers to social communication. Data were analyzed descriptively through qualitative data reduction, presentation, and conclusion drawing, ensuring data validity through triangulation. The results indicate that barriers to social communication in children are evident in low levels of peer interaction, limited speaking skills, lack of participation in group activities, and suboptimal responses to teacher direction. The application of interactive, adaptive, and child-centered learning strategies, such as role-playing, group games, interactive storytelling, and individual mentoring, has been shown to gradually improve children's social communication skills. This study confirms the crucial role of teachers in creating a learning environment that supports the development of social communication in early childhood. The application of interactive, adaptive, and child-centered learning strategies, such as role-playing, group games, interactive storytelling, and individual mentoring, has been shown to gradually improve children's social communication skills. This study confirms the crucial role of teachers in creating a learning environment that supports the development of social communication in early childhood.